Achieving an extra-high-strength yet ductile steel by synergistic effects of TRIP and maraging. Issue 7 (3rd July 2023) - Yang, Bo; He, Qiong; Wang, Hui; Wang, Cunyu; Guo, Fengjiao; Hu, Rong; Wang, Chang; Fan, Guohua; Wang, Qingyuan; Cao, Wenquan; Huang, Chongxiang
Abstract : A novel type of austenite–martensite dual-phase laminate steel with a yield strength of 2.2 GPa, ultimate tensile strength of 2.5 GPa, uniform elongation of 9.4% and total elongation of 12% was produced. Such unexpectable mechanical properties were mainly due to the synergistic strengthening of nanolaminate microstructure, high densities of dislocations and nanoprecipitates. The high uniform elongation at very high stress could be attributed to the strongly enhanced work hardening rate, mainly enabled by transformation-induced plasticity (TRIP) of the austenite reverted by annealing, as well as the cooperative deformation and stress/strain partitioning between the austenite–martensite stacked nanolaminate. GRAPHICAL ABSTRACT: UF0001 IMPACT STATEMENT: This work verifies an effective strategy of combining TRIP and maraging to achieve both ultrahigh strength and high ductility of steel.